(untitled) (Innovation in Woodworking Industry and Engineering design, 2026)
Subject of the investigation is the prognostication of the resistance of structural three- and multilayer particleboards (SPB) to continuous static bending load under the conditions of rela-tively dry environment. The theoretical prerequisites of the development are the rheological model of SPB and the schematic diagram of their deformation during continuous load, the algo-rithm and the nomogram to determine the stiffness of SPB on the basis of their simulation model of a “double T-beam” and the regression dependences of the moduli of elasticity of SPB with various thicknesses on their volumetric density. An algorithm and a nomogram to determine the continuous load factor of SPB to prognosticate their resistance as structural elements in furniture and building structures have been pro-posed. The creep coefficient of composite particleboards under operating conditions has been determined.